SHARK SPECIES COMPOSITION AND DISTRIBUTION OF FISHING GROUND BASED ON FISHING GEAR IN CILACAP OCEAN FISHERY PORT - Novianto, Dian; Widiarto, Santoso Budi; Muslim, Anhar; Aji, Miftah Wahyu Purnomo; Prakoso, Kukuh (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2024)
This study focuses on shark species composition, fishing techniques, and geographical distribution in the South Java Waters of Cilacap Ocean Fishing Port (COFP) during 2023. From the data collected, 18 shark species from 8 families were landed, with Alopias superciliosus as the dominant species (29%), followed by Carcharhinus falciformis (25%), and Alopias pelagicus (18%). Shark fishing was conducted with various gears such as tuna longline, drift longline, longline, drift gillnet, and bottom gillnet, with drift longline being the most effective gear with the largest contribution to the catch. Most of the sharks caught were categorized as endangered (EN) and vulnerable (VU) based on the IUCN conservation list, and listed in Appendix II of CITES. The results show that the geographic distribution of shark fishing grounds covers a wide area from the coast to the Indian Ocean, with high concentrations in the waters around Kebumen to the south of Yogyakarta. Fishing activities often overlap between fishing gears, increasing the risk of overfishing. Length distributions and maturity rates of sharks also indicate that many mating-ready adults are being caught, threatening slow population regeneration. To ensure the sustainability of shark populations and maintain the balance of marine ecosystems, a holistic and data-driven management strategy is needed. This includes strengthening regulations, raising public awareness through conservation education, and developing collaborative approaches involving fishers, government, and conservation organizations. Consistent law enforcement is also key in minimizing violations and ensuring the sustainability of shark fisheries in Indonesia.